2012
DOI: 10.1002/cphc.201101029
|View full text |Cite
|
Sign up to set email alerts
|

Azafullerene C59N–Phthalocyanine Dyad: Synthesis, Characterisation and Photoinduced Electron Transfer

Abstract: The synthesis of a new azafullerene C(59)N-phthalocyanine (Pc) dyad is described. The key step for the synthesis of the C(59)N-Pc dyad was the formation of the C(59)N-based carboxylic acid, which was smoothly condensed with hydroxy-modified Pc. The structure of the C(59)N-Pc dyad was verified by (1)H and (13)C NMR spectroscopy, IR spectroscopy, UV/Vis spectroscopy and MS measurements. The photophysical and electrochemical properties of the C(59)N-Pc dyad were investigated in both polar and non-polar solvents b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 59 publications
(23 reference statements)
2
31
1
Order By: Relevance
“…In the case of C 59 N, addition of the first malonate moiety decreases the LUMO energy by 0.06 eV, specifically from −3.89 eV for (C 59 N) 2 to −3.95 eV for monoadduct 2 . This is analogous to observations in previous studies, with opposing trends being reported for C 60 monoadducts. Addition of the second malonate to C 59 N forming bisadduct (±)‐ 3 raises the LUMO level to −3.81 eV, 0.08 eV higher than that of the parent (C 59 N) 2 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of C 59 N, addition of the first malonate moiety decreases the LUMO energy by 0.06 eV, specifically from −3.89 eV for (C 59 N) 2 to −3.95 eV for monoadduct 2 . This is analogous to observations in previous studies, with opposing trends being reported for C 60 monoadducts. Addition of the second malonate to C 59 N forming bisadduct (±)‐ 3 raises the LUMO level to −3.81 eV, 0.08 eV higher than that of the parent (C 59 N) 2 .…”
Section: Resultssupporting
confidence: 91%
“…In these, the addend is bound at the 2‐position adjacent to the nitrogen atom following electrophilic aromatic substitution with electron‐rich arenes or Mannich‐type nucleophilic substitution reactions (Figure a) . Several C 59 N‐based donor–acceptor hybrids have been synthesized, incorporating phthalocyanines, corrole, porphyrins, perylene, polycyclic aromatic hydrocarbons, ferrocene, or gold nanoparticles, and were shown to participate in ultrafast energy‐ or electron‐transfer processes. Notably, in a more recent example, an oligophenylenevinylene wire was conjugated to C 59 N, yielding an ultralong charge‐separation lifetime of 20 ms .…”
Section: Introductionmentioning
confidence: 99%
“…Re--cently, there have been substantial increases in power conversion efficiencies in DSSCs using unsymmetrically substituted ''push-pull'' zinc phthalocyanines with bulky substituents. 47--50 Among them, phthalocyanines have been also covalently and non--covalently connected with different electron acceptor carbon nanostructures, 51,52 such as C 60 , 53--56 C 59 N, 57 carbon nanotubes, 58 perylenebisi--mides 59--66 and the photoinduced electron and/or energy transfer properties of these systems have been studied for their use as artificial photosynthetic systems and in or--ganic solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The titration results establish the effective development of electronic interactions between the two species,w ithin the [10]CPP'(C 59 N) 2 &[10]CPP complex, in the excited state. Notably,t he absence of emission in the NIR range,t hat is, 800-950 nm, corresponding to the azafullerene emission, [26,27] implies weak, if any,s inglet-singlet energy transfer from [10]CPP to (C 59 N) 2 .W hile full TDDFT calculations are not possible on systems of this size,the PL response is consistent In conclusion, we rationalize that bis(azafullerene) (C 59 N) 2 can be complexed by two [10]CPP macrocycles, with the first one stabilizing the binding of the second by maximizing p-p,C ÀH-p,a sw ell as attractive London dispersion interactions,f orming [10]CPP'(C 59 N) 2 &[10]CPP. Theoretical simulations reveal an unexpected tilted structure with an asymmetric arrangement of the [10]CPPs on the (C 59 N) 2 .M oreover,electrochemical as well as photoluminescence studies deliver meaningful insight for the electronic communication.…”
mentioning
confidence: 99%